Rousseau et les Pongos - Thomas Robert (Revue de Primatologie)
In note X of the Discours sur l’origine et les fondements de l’inégalité parmi les hommes, Rousseau calls the Pongoes up in the context of his anthropology. The question is to determine wether the Pongoes are human beings. A positive answer would confirm Rousseau’s definition of human essence, which is represented by the natural man described in the first part of the Discours. Rousseau criticises the narratives of travellers, who consider, at best, the Pongoes as beasts or, at worst, as monsters. After having demonstrated the mistakes committed by the travellers with respect to their observations of the Pongoes, Rousseau proposes an empirical method leading to the elaboration of an ethnology of all societies. In this article, I analyse the relation between humanity and animality before studying the note on the Pongoes, which leads me to argue for a Rousseauistic approach in primatology.